Barriers to suicide research are also barriers to suicide prevention:Insights from conducting a mixed-methods project in oncology - Judith Hirschmiller; Tamara Schwinn; Jörg Wiltink; Manfred E. Beutel; Rüdiger Zwerenz; Elmar Brähler; Mareike Ernst (SSM - Mental Health, 2025)
Cancer patients are at risk for suicidal crises. There is a need for more research concerning specific risk/protective factors and knowledge about barriers and resources of prevention efforts in clinical practice. This contribution reports on difficulties during the realization of a research project that aimed to address these research gaps, among other approaches, via a patient survey and an interview study with healthcare professionals (HCPs). Throughout recruitment and implementation, we documented the barriers encountered and systematically analyzed them.We identified three main categories of obstacles toward the research endeavor that also hold meaning for the efficacy of suicide prevention: First, suicidal thoughts and behaviors are not (allowed to be) an issue in oncology, subsuming the denial of their occurrence, the minimization of their relevance, the alleged appropriateness of the construct to oncology, and the rejection of responsibility; second, prevailing suicide myths, in particular of iatrogenic harm; and third, strong, negative emotional reactions undermining dialogue.We interpret these experiences against previous considerations of dysregulated responses to suicidal patients in the healthcare setting and analyze their causes and functions. These findings highlight the urgent need for structured education on suicide prevention across medical disciplines, particularly in oncology. Addressing both knowledge gaps and emotional barriers among HCPs is crucial for fostering a proactive, evidence-based approach to suicide prevention. Future efforts should focus on integrating suicide risk assessment and intervention strategies into routine cancer care, alongside improved interdisciplinary collaboration and institutional support.